Governance and Women's Economic and Political Participation : Power Inequalities, Formal Constraints and Norms - Milazzo, Annamaria (World Bank, Washington, DC, 2017)
What role do institutional constraints and social norms play in determining persistent gender gapsin economic and political participation and have institutional reforms been successful in reducing these gaps? This paper argues that, at the roots of current gender inequalities, there are traditional patriarchal social structures in which power is unequally distributed, with men traditionally holding authority over women. The power imbalance is manifested in governance arrangements, of which the author consider discriminatory formal laws and adverse gender norms that perpetuate gender inequality. The author reviewed the evidence on the effectiveness of reforms addressing gender inequality and applied via formal law changes. Aware of endogeneity issues as reforms may be adopted in countries where attitudes toward women had already been improving, we focus on micro-empirical studies that tackle this challenge. The evidence suggests that some reforms have been successful reducing inequalities. Power and norms can shift and sometimes temporary interventions can deliver long-term results. There are, however, enormous challenges posed by power inequalities and inherent social norms that are slow-moving. Formal laws can remain ineffective or cause a backlash because: i) the law is poorly implemented and/or people are not aware of it; ii) informal systems and social norms/sanctions are stronger; iii) powerful groups (in our case, men) may oppose these changes. Finally, reforms that improve women’s economic opportunities can create the conditions to increase political participation and vice-versa, thereby generating a self-reinforcing cycle of inclusion.